2021
DOI: 10.3390/jpm11090877
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics Variability of Lipid-Lowering Therapies in Familial Hypercholesterolemia

Abstract: The exponential expansion of genomic data coupled with the lack of appropriate clinical categorization of the variants is posing a major challenge to conventional medications for many common and rare diseases. To narrow this gap and achieve the goals of personalized medicine, a collaborative effort should be made to characterize the genomic variants functionally and clinically with a massive global genomic sequencing of “healthy” subjects from several ethnicities. Familial-based clustered diseases with homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…The most common side effects of PCSK9 inhibitors are injection-site reactions and Influenza-like symptoms (Gürgöze et al, 2019). Pharmacogenomic studies carried out in individuals with familial hypercholesterolemia have reported that the efficacy of PSCK9 inhibitors such as evolocumab and alirocumab are affected by polymorphisms in apo B, low density lipoprotein receptor (LDL-R) and LDL-R adapter protein 1 genes (Hindi et al, 2021). Remarkably, a recent metanalysis provided evidence that the efficacy of PCSK9 inhibitors could be similar for different ethnicities (Sawant and Wang, 2023).…”
Section: Pcsk9 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common side effects of PCSK9 inhibitors are injection-site reactions and Influenza-like symptoms (Gürgöze et al, 2019). Pharmacogenomic studies carried out in individuals with familial hypercholesterolemia have reported that the efficacy of PSCK9 inhibitors such as evolocumab and alirocumab are affected by polymorphisms in apo B, low density lipoprotein receptor (LDL-R) and LDL-R adapter protein 1 genes (Hindi et al, 2021). Remarkably, a recent metanalysis provided evidence that the efficacy of PCSK9 inhibitors could be similar for different ethnicities (Sawant and Wang, 2023).…”
Section: Pcsk9 Inhibitorsmentioning
confidence: 99%
“…The effect of these genes would depend on the specific statin considered (Zineh, 2007). Similarly, polymorphisms in genes involved in lipid metabolism such as ABCA 1, LDL-R and HMGCR can influence the efficacy of statins (Hindi et al, 2021). Moreover, there is evidence of interracial differences in the response to statins (Lee et al, 2005).…”
Section: Statinsmentioning
confidence: 99%
“…It has been observed that the NPC1L1 transporter primarily absorbs dietary cholesterol, with plant sterols and stanols being absorbed to a lesser extent (3,4) . The e ux transporters, ABCG5 and ABCG8, have been identi ed as the main proteins responsible for the active transport of plant sterols back to the intestinal lumen (4,5) . The sterols are assimilated into chylomicrons that are rich in cholesterol and carried to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recently blood-lipid drugs are antisense or monoclonal antibodies for genes implicated in lipid regulation, such as APOC3 and ANGPTL3. However, it is necessary to consider polygenic risk scores to identify the best pharmacological treatment [6,7] alongside nutrient-gene interactions.…”
Section: Introductionmentioning
confidence: 99%